2018
DOI: 10.3389/fnmol.2017.00438
|View full text |Cite
|
Sign up to set email alerts
|

The GlyT1 Inhibitor Bitopertin Ameliorates Allodynia and Hyperalgesia in Animal Models of Neuropathic and Inflammatory Pain

Abstract: Background: Chronic pain conditions are difficult to treat and the therapeutic outcome is frequently unsatisfactory. Changes in excitation/inhibition balance within the dorsal horn contribute to the establishment and persistence of chronic pain. Thus, facilitation of inhibitory neurotransmission is a promising approach to treat chronic pain pharmacologically. Glycine transporter 1 (GlyT1) plays an important role in regulating extracellular glycine concentrations. Aim of the present study therefore was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…Our results to amelioration of chronic NP are in accordance with other studies indicating that GlyT-1 or 2 inhibitors attenuate NP in rodents [ 6 , 7 , 23 , 25 , 26 ]. As mentioned above, GlyT-1 and 2 play crucial roles in the regulation of glycinergic inhibitory neurotransmission, and drugs that affect these transporters are able to affect systems operated by glycine.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results to amelioration of chronic NP are in accordance with other studies indicating that GlyT-1 or 2 inhibitors attenuate NP in rodents [ 6 , 7 , 23 , 25 , 26 ]. As mentioned above, GlyT-1 and 2 play crucial roles in the regulation of glycinergic inhibitory neurotransmission, and drugs that affect these transporters are able to affect systems operated by glycine.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, NFPS failed to show acute antiallodynic action, but it produced antiallodynic effect upon chronic treatment. Armbruster and coworkers showed that bitopertin, a GlyT-1 inhibitor, did produce antiallodynic effect following acute treatment in mice [ 23 ]. They have also proved that long-term treatment produces antiallodynic effect without noticeable side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, D-cycloserine and other glycine site ligands may improve social cognition in ASDs and genetically related Rett syndrome [115,116]. Other indications under consideration include drug abuse [117], amyotrophic lateral sclerosis [22], chronic pain [118] and facilitation of psychosocial-cognitive behavioural therapies for anxiety disorders [119]. potential conflict of interest.…”
Section: General Discussion and Broader-clinical Relevance Of The Prementioning
confidence: 99%
“…Bitopertin is a highly selective GlyT1 inhibitor that underwent several clinical trials, notably for the treatment of negative symptoms associated with schizophrenia (Bugarski-Kirola et al, 2017;Hirayasu et al, 2016;Kantrowitz et al, 2018;Rofail et al, 2016), obsessive-compulsive disorder (Roche, 2012) and β-thalassaemia (Roche, 2017;Taher et al, 2018). Moreover, recent pre-clinical studies suggested that bitopertin could have a therapeutic potential at managing neuropathic pain and improving cognition (Armbruster et al, 2018;Castner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%